2002
DOI: 10.1074/jbc.m207747200
|View full text |Cite
|
Sign up to set email alerts
|

Molecular Mechanism for Orienting Membrane and Actin Dynamics to Nascent Cell-Cell Contacts in Epithelial Cells

Abstract: The small GTPase Rac1 has been implicated in regulation of cell migration and cell-cell adhesion in epithelial cells. Little is known, however, about the spatial and temporal coordination of Rac1 activity required to balance these competing processes. We fractionated endogenous Rac1-containing protein complexes from membranes of Madin-Darby canine kidney cells and identified three major complexes comprising a Rac1⅐PAK (p21-activated kinase) complex, and 11 S and 16 S Rac1 complexes. Significantly, Rac1 shifts … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
43
0
2

Year Published

2004
2004
2014
2014

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 51 publications
(48 citation statements)
references
References 25 publications
3
43
0
2
Order By: Relevance
“…Rac1 is a GTPase that belongs to the Ras superfamily of small GTP-binding proteins. Further, the complex of Rac1 and ANXA2 is localized to cadherin-mediated cellcell contacts (85). It is possible that the loss of ANXA2 may retard Rac1 activation followed by JNK inactivation.…”
Section: Discussionmentioning
confidence: 99%
“…Rac1 is a GTPase that belongs to the Ras superfamily of small GTP-binding proteins. Further, the complex of Rac1 and ANXA2 is localized to cadherin-mediated cellcell contacts (85). It is possible that the loss of ANXA2 may retard Rac1 activation followed by JNK inactivation.…”
Section: Discussionmentioning
confidence: 99%
“…Reestablishment of endothelial junction integrity occurring between 1 and 2 hours after thrombin exposure corresponded with the time course of Cdc42 activation. Rac1 was reported to be present in the contact areas between epithelial cells during the initial stages of cell-cell junction formation 35,36 and is involved in actin cytoskeleton remodeling and lamellipodia formation. 35,37,38 In the present study, we observed that thrombin did not induce activation of Rac in endothelial cells under these conditions.…”
Section: Discussionmentioning
confidence: 99%
“…Annexin II and ALCAM, both being metastasis-associated proteins (Wu et al, 2002;Degen et al, 1998), synergistically contribute to the metastatic progression of fibrosarcoma cells (Choi et al, 2000). Moreover, annexin II has been shown to be a binding partner of a 16 S Rac complex that localizes rapidly to cellcell contact sites (Hansen et al, 2002). As shown in Fig.…”
Section: α-Catenin May Be the Link Between F-actin And Alcammentioning
confidence: 99%